Pengembangan Kewirausahaan Bagi Mahasiswa Melalui Program Wirausaha Merdeka Dengan Inovasi Pengolahan Daun Kelor (Moringa Oleifera) Menjadi Teh Keloruma - Hasmarani, Hesti; Arif, Muhammad (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2026)
The high unemployment rate among college graduates increases the importance of developing an entrepreneurial spirit among students. The Independent Entrepreneurship Program, which is part of the Independent Learning Campus (MBKM), provides students with the opportunity to develop business ideas based on local potential. This study aims to analyze the development strategy of the herbal tea business "Tea Keloruma" made from moringa leaves (Moringa oleifera), through a SWOT analysis approach and the preparation of a Business Model Canvas (BMC). The method used is qualitative descriptive analysis with a SWOT approach to identify internal factors (strengths and weaknesses) and external factors (opportunities and threats) faced in business development. The results of the analysis show that Tea Keloruma is in quadrant I in the SWOT diagram, which recommends implementing an aggressive strategy in the form of strengths-opportunities (SO). This strategy emphasizes the use of moringa leaf nutrition and healthy lifestyle trends to expand the market. Meanwhile, weaknesses such as lack of digital promotion and low consumer understanding are overcome through market education and branding strengthening. This study also found that Tea Keloruma business model includes collaboration with local farmers, broad consumer segmentation, and distribution strategies through social media and UMKM bazaars. With an innovative approach that focuses on local potential, Tea Keloruma is expected to be a significant example in the development of student entrepreneurship that provides economic and social impacts.